Analysis of mistakes made in reproduction of English words - Laptėvaitė , I. (Psichologija, 1969)
This is an account of the analysis of mistakes made in memorization of English words in the course of our experimental study. The following was observed: l. Retention of pronunciation is inferior to retention of graphic form of words. This phenomenon can be attributed to the lower carrying capacity of the auditory canal as compared with the visual canal. 2. Proactive interference is the cause of the greatest amount of mistakes. 3. Association value of phones influences memorization of pronunciation. Association value of words of not too remote frequencies affects memorization of graphic form only slightly. 4. Simplification and omission of details manifests itself in memorization of words especially compound ones.